2013
DOI: 10.1186/1472-6963-13-457
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic data for neurological conditions in interRAI assessments in home care, nursing home and mental health care settings: a validity study

Abstract: BackgroundThe interRAI suite of assessment instruments can provide valuable information to support person-specific care planning across the continuum of care. Comprehensive clinical information is collected with these instruments, including disease diagnoses. In Canada, interRAI data holdings represent some of the largest repositories of clinical information in the country for persons with neurological conditions. This study examined the accuracy of the diagnostic information captured by interRAI instruments d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 33 publications
1
74
1
Order By: Relevance
“…Main strengths of our study include the multicenter design, leading to extensive data collection from a large, real and representative ). Moreover, the comprehensive assessment implemented in our setting is similar to the Minimum Data Set applied in other international contexts, such as nursing facilities in the United States, and to subsequent derived geriatric assessment tools [33], and includes a comprehensive assessment with validated cognitive and functional measures.…”
Section: Discussionmentioning
confidence: 99%
“…Main strengths of our study include the multicenter design, leading to extensive data collection from a large, real and representative ). Moreover, the comprehensive assessment implemented in our setting is similar to the Minimum Data Set applied in other international contexts, such as nursing facilities in the United States, and to subsequent derived geriatric assessment tools [33], and includes a comprehensive assessment with validated cognitive and functional measures.…”
Section: Discussionmentioning
confidence: 99%
“…risk of harm. The reliability and validity of the RAI-MH have been previously established in a variety of studies (Foebel et al 2013; Gibbons et al 2008; Hirdes et al 2008; Jones et al 2010; Martin et al 2009). …”
Section: Methodsmentioning
confidence: 97%
“…Any text diagnoses in this section that referred to head trauma, concussion, closed head injury, head injury, or acquired brain injury was used to capture cases of TBI. This method of capturing TBI (i.e., item and text entries) has been previously validated; (23) it had a sensitivity of 0.23, a specificity of 0.99, a positive predictive value of 0.22, and a kappa statistic of 0.22 when compared to linked data from the National Ambulatory Care Reporting System (NACRS) and the Canadian Institute for Health Information (CIHI). (24) …”
Section: Methodsmentioning
confidence: 99%
“…(15) Foebel and colleagues (23) found that the validity of items related to diagnoses of Alzheimer’s disease and other dementia (sensitivity of 0.76; specificity of 0.89; PPV of 0.53; kappa statistic of 0.55), parkinsonism (sensitivity of 0.83; specificity of 0.98; PPV of 0.59; kappa statistic of 0.68), and multiple sclerosis (sensitivity of 0.90; specificity of 1.00; PPV of 0.77; kappa statistic of 0.83) was acceptable when compared to linked NACRS and CIHI data. (24) …”
Section: Methodsmentioning
confidence: 99%